Toxic Relationship Pada Dewasa Awal di SMK Telekomunikasi Telesandi Bekasi - Aryani, Eka Yeni; Netty Merdiaty (CV. ITTC INDONESIA, 2024)
Relationships between partners are basically related to gender equality, without the concept of dominance in heterosexual relationships. However, many couples experience toxic relationships. Interpersonal communication in this kind of relationship tends to be negative, so it will create feelings of discomfort. This research aims to determine the occurrence of toxic relationships based on certain aspects. The phenomenon of toxic relationships in interpersonal communication between young adult students and students. The method used is descriptive quantitative with normality tests and characteristic tests. The sample used in this research was 105 respondents selected using purposive sampling technique. The results in this study show a value of 58.34% which indicates the medium category and the significance value shows 0.74. This means that in this research, with the toxic relationship variable, the data obtained is normal and there is a toxic relationship in the bad temper aspect at Telekomunikasi Telesandi Bekasi Vocational School in class 15 and class 16.